Use of heart-rate variability to examine readiness to perform in response to overload and taper in swimmers - Sanpasitt, C.; Intiraporn, C.; Yimlamai, T. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This study aimed to compare the effectiveness of complex training (CT) with inclined versus horizontal speed bounding on sprint acceleration ability and neuromuscular performance in youth male sprinters.